2019
DOI: 10.1155/2019/2509059
|View full text |Cite
|
Sign up to set email alerts
|

HCV Eradication with Direct-Acting Antivirals Does Not Impact HCC Progression on the Waiting List or HCC Recurrence after Liver Transplantation

Abstract: Background The introduction of direct-acting antivirals (DAA) for HCV has led to high rates of HCV eradication. Treatment of patients awaiting liver transplantation (LT) has been controversial. Recent data suggests that DAA treatment may accelerate recurrent HCC. The impact of DAA on delisting for HCC progression or recurrent HCC post-LT has not been well characterized. Methods A retrospective review of both waitlist patients and LT recipients at a single institution was performed. Patient demographics, HCV tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…( 34,35 ) Three single‐center retrospective cohort studies addressed the effect of DAAs and HCC wait‐list progression and recurrence following transplantation. ( 20,21,36 ) Opposing results were previously reported. A nonsignificant higher rate of wait‐list tumor progression and post‐LT recurrence in patients treated with DAAs before transplantation was observed in an Italian study, ( 20 ) whereas a reduced risk of wait‐list tumor progression was observed in a cohort from the University of California, San Francisco.…”
Section: Discussionmentioning
confidence: 75%
“…( 34,35 ) Three single‐center retrospective cohort studies addressed the effect of DAAs and HCC wait‐list progression and recurrence following transplantation. ( 20,21,36 ) Opposing results were previously reported. A nonsignificant higher rate of wait‐list tumor progression and post‐LT recurrence in patients treated with DAAs before transplantation was observed in an Italian study, ( 20 ) whereas a reduced risk of wait‐list tumor progression was observed in a cohort from the University of California, San Francisco.…”
Section: Discussionmentioning
confidence: 75%
“…Early generation DAA regimens, such as SOF + RBV, had lower SVR rates, in line with clinical trial outcomes. Emamaullee et al found only 57% SVR with a 24‐week course of SOF + RBV. In our analysis, suboptimal regimens resulted in an SVR of 76.3%.…”
Section: Discussionmentioning
confidence: 99%
“…There are several issues relevant to DAA therapy among patients with HCC. First, initial data suggested a potential increased risk of HCC recurrence, although subsequent studies did not support these findings . Second, in response to the controversy around HCC recurrence risk, the timing of DAA therapy in relation to HCC management became a point of debate .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in the immune function may not affect the HCC recurrence rate according to the report that HCV eradication by DAA does not impact rates of delisting for HCC progression or rates of HCC recurrence post-liver transplantation. 46 We previously reported that the altered immune response after DAA therapy might affect the severity of HCC recurrence, not the recurrence rate, 47 but the conclusion was withheld because there was a problem with the statistical analysis. Considering that many clinicians have thought that an unexpected recurrence has occurred, [14][15][16][17] the promotion of recurrence by DAA might be a phenomenon that is extremely rare but possible in practice so that one cannot show a statistically significant difference.…”
Section: Discussionmentioning
confidence: 99%